To find the x-intercept, you let y=0 and solve for x.
To find the y-intercept, you let x=0, and solve for y.
For the first one,
x-intercept: 0= (x-1) / (x+2), solving you get x=1. So (1,0) is the x-intercept.
y-intercept: y = (0-1)/(0+2) = -1/2. So (0, -1/2) is the y-intercept.
For the second one,
x-intercept: 0 = 5/(x^2+6x-6). This has no solution, so it does not exist.
y-intercept: y = 5/ (0+0-6) = -5/6. So (0, -5/6) is the y-intercept.
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?